Human resource prerequisite for digital economy development - Majovski, Irina; Davitkovska, Elena (Institute of Economics - Skopje, 2017)
The level of digital economy development pertains to digitalization and high level of ICT usage as well as deployment of hightech solutions for achieving market value, higher productivity and innovation. To capitalize on the opportunities that have emerged from high-tech solutions, businesses need digitally skilled workforce that can deploy advanced technology in daily business operations. Thus, digital skill upgrading has become a key priority for most businesses and key priority for every economy to compete globally. A combination of digital skills and entrepreneurial skills would be main prerequisite for success in future as workforce with such skillset will be able to carry out work in a technology-rich environment and to seize the opportunities derived from technology advancements in business innovations.
Keywords: digital economy; digital skills; human resources; ICT development